The International Fragile X Premutation Registry: building a resource for research and clinical trial readiness. Issue 12 (14th June 2022) - Hessl, David; Rosselot, Hilary; Miller, Robert; Espinal, Glenda; Famula, Jessica; Sherman, Stephanie L; Todd, Peter K; Cabal Herrera, Ana Maria; Lipworth, Karen; Cohen, Jonathan; Hall, Deborah A; Leehey, Maureen; et al.
Abstract : FMR1 premutation cytosine-guanine-guanine repeat expansion alleles are relatively common mutations in the general population that are associated with a neurodegenerative disease (fragile X-associated tremor/ataxia syndrome), reproductive health problems and potentially a wide range of additional mental and general health conditions that are not yet well-characterised. The International Fragile X Premutation Registry (IFXPR) was developed to facilitate and encourage research to better understand the FMR1 premutation and its impact on human health, to facilitate clinical trial readiness by identifying and characterising diverse cohorts of individuals interested in study participation, and to build community and collaboration among carriers, family members, researchers and clinicians around the world. Here, we describe the development and content of the IFXPR, characterise its first 747 registrants from 32 countries and invite investigators to apply for recruitment support for their project(s). With larger numbers, increased diversity and potentially the future clinical characterisation of registrants, the IFXPR will contribute to a more comprehensive and accurate understanding of the fragile X premutation in human health and support treatment studies.